Characterization of Polyglycerol Polyricinoleate Formulations Using NMR Spectroscopy, Mass Spectrometry and Dynamic Light Scattering. (23rd September 2012) - Orfanakis, Andreas; Hatzakis, Emmanuel; Kanaki, Katerina; Pergantis, Spiros A.; Rizos, Apostolos; Dais, Photis
Abstract: Three different analytical techniques, namely NMR spectroscopy, mass spectrometry and dynamic light scattering, were used to unravel the structure and morphology of polyglycerol polyricinoleate (PGPR). This material is used as an emulsifier in the preparation of chocolate and other confectionary products. The use of 1D and 2D NMR techniques led to the distinction of two separate entities in commercial ricinoleic acid (RA) and PGPR samples, namely the monomeric and oligomeric RA (estolides). 1 H and 13 C spectra of PGPR confirmed the presence of polyglycerol moieties of various lengths being esterified by RA and estolides and to a lesser extent by oleic and linoleic acids. 13 C‐NMR DOSY experiments demonstrated the occurrence of several species in PGPR. Electrospray Ionization and tandem Mass Spectrometry succeeded in identifying the presence of over 30 glycerol/polyglycerol species containing n glycerol moieties with n = 1–6 esterified by monomeric and oligomeric RA molecules. Dynamic light scattering contributed to the characterization of PGPR morphology. The PGPR mixture contains relatively small‐sized entities (monomers, dimmers, trimmers) and larger aggregates resulted from chain association. The percentage of larger aggregates is minimal compared to small‐sized species.